Using Oral History and Archival Exploration to Forge a Path to the Past: A GeneralSurvey of the Adult Education Opportunities Available to African American Adults inCincinnati, Ohio, 1930-1949 - Lisa Merriweather Hunn (Adult Education Research Conference, 2004)
This paper provides a local history of African American adult education inCincinnati. It identifies two categories of learning opportunities: learning in thecommunity and learning by experience. This study also identifies AAAE’s liberaleducation platform as a major influence over those opportunities because it indirectlysupported Jim Crow racism. This history of African American adult education for manyyears suffered from what Franklin (1989) called the “conspiracy of silence” (p. 44) whichresulted in people of African descent being viewed ahistorically within adult education.This history has not been sufficiently explored (Neufeldt & McGee, 1990). Most of whatis available on African American adult education looks at institutions, agencies, leaders,and philosophies (Neufeldt & McGee, 1990; Peterson, 1996) but few include socio -historical observations about the African American learners from their perspectives. Toensure that adult learners’ voices are included in historical narratives, historians shouldnot just limit themselves to written sources but should also consider using oral history.The purpose of this oral history project was to provide a descriptive account of adulteducation for African Americans in Cincinnati, Ohio, during the 1930s and the 1940s.The following research questions were addressed: 1. What adult educationalopportunities were available to African Americans during this time period? 2. To whatextent were these opportunities influenced by racism?